Pro-inflammatory B Cells Predict Progressive Minimal Early Renal Allograft Inflammation Which Is Associated with Poor Graft Outcomes. (July 2018) - Sharma, Akhil; Cherukuri, Aravind; Chittka, Dominik; Mehta, Rajil; Hariharan, Sundaram; Rothstein, David
Abstract : Introduction: The clinical significance of minimal tubulointerstitial inflammation (MTI: 't'+'i' scores 0.5-1.5) and Banff Borderline changes (BBC: 't' + 'i' scores 2-3.0) in early renal allograft biopsies is unclear. The rate and significance of progression of these lesions to late acute rejection (AR) also remains unknown. In this study, we assessed the clinical significance of early tubulointerstitial inflammation (< Banff 1A rejection). Methods: Our center performs 2 protocol biopsies (3 & 12 months) along with for-cause biopsies. This allowed us to assess the clinical impact of early (0-4 months) MTI and BBC on graft outcomes. Furthermore, we examined the relationship between peripheral blood B cell cytokines and early MTI and BBC. Results: 208/372 patients transplanted between 1/13-11/14 had either no inflammation (NI, 36%, 76/208), MTI (34%, 70/208) or BBC (30%, 62/208) on early biopsies (0-4 months). Patients with NI (17%), MTI (24%) and BBC (34%) at 0-4 months exhibited increasing rates (in parentheses) of progression to AR (≥Banff 1A) by 12mo. Further, patients with MTI or BBC (0-4 months) had increased graft loss or impending graft loss (eGFR<30ml/min and >30% decline from baseline) by 50 months when compared to those with NI (Fig. 1A). While graft outcome in the NI group was not affected by progression to late AR (p=0.85), patients with early MTI (Fig 1B) or BBC (Fig 1C) had significantly worse outcomes if they developed late AR. Thus, early allograft inflammation (either MIT or BBC) was not only associated with increased progression to late AR, but those who progressed had worse outcomes. Thus, MTI and BBC, particularly in patients who will progress, represent a clinical phenotype at risk for poor outcomes. Clinical factors, including 3 months histology, could not predict progression of MTI or BBC to late AR. Based on previous results, we asked whether peripheral blood B cell cytokines could predict progression to AR in these patients. 72 patients with either MTI (n=26) or BBC (n=46) had their B cells and cytokines analyzed at 3 months. IL-10:TNFα expression ratio within T1 transitional B cells was significantly lower in both the MTI (6.3X) and BBC (4.6X) patients who progressed compared to those who were stable (p<0.0004). Finally, a low T1 B cytokine ratio strongly predicted late progression to AR (ROC AUC 0.94 p<0.0001, Sen 92%, Spec 88%) in patients with early allograft inflammation (MIT or BBC). Conclusion: Patients with early minimal allograft inflammation that progress to AR at 1 year represent a high-risk cohort for graft dysfunction. This group could be identified by 2-4 mo, using the T1 B IL-10:TNFα ratio – allowing early intervention.